The Effect of Steel Fiber Content on the Splitting Tensile Strength of steel fiber reinforced concrete (SFRC) - Sitorus, Mentari Septanya; Afiah, Indah Nur; Ibrahim, Zulfadli; Muhibuddin, Andi Firman (Journal of Civil Engineering, 2025)
Concrete is a composite material consisting of two main components namely aggregate and cement mortar as a binder. Concrete has high compressive strength but weak tensile strength. The addition of fiber in concrete can improve ductile behavior before collapse, inhibit the growth of crack expansion and increase durability. This study aims to examine the effect of fiber content on the mechanical properties of fiber concrete. The fibers used were ssteel fibers with hooked end, and l/d ratio = 67,7 mm with normal concrete quality f’c = 25 MPa. The percentage of fiber content used in this study was 0%, 0,1%, 0,2%, 0,3%, 0,5%, 0,75%, 1%, 1,5% and 2%. The results showed that the addition of fiber in concrete was able to increase the split tensile strength by 7 – 117%. Fiber concrete has higher ductility than normal concrete. This is indicated by the high deflection of fiber concrete compared to the deflection of normal concrete under load.